Shift in Cropping Pattern in Sewage Irrigated Farming Systems: A case study - Singh, Magan (Indian Journal of Agroforestry, 2020)
A survey was carried out in sewage irrigated fields of village 'Ganjia' (80 years of sewage irrigation) and 'Dandi' (20 years of sewage irrigation) of Allahabad to find out the crop diversity and shift in cropping pattern in different years (comparison of 1990 to 1996 and 1998) on randomly selected 25 farmers through personal interviews. The samples were analysed for copper and lead as heavy metal content in potato produced from these farms.There were 25 cropping patterns followed, and there are basically two major cropping sequences occurred i.e. rice-wheat-vegetables and rice-potato-vegetables. Great diversity occurred amongst crops that were replaced in order one by another on its area basis. Major cropping pattern were shifted by vegetables, fruits and flowers. There were shift in cropping pattern towards more remunerative vegetable crops, which could lead to disastrous heavy metal toxicity in the food chain. On an average the samples of potato contained 30 ppm of lead, 39 ppm of copper, which was 3.08 times and 1.96 times higher than the toxic levels for lead and copper, respectively. Floriculture could offer a viable alternative cropping system in the area studied.